Safety Proﬁle of Secukinumab in Treatment of Patients with Psoriasis and Concurrent Hepatitis B or C: A Multicentric Prospective Cohort Study - Hsien-Yi Chiu; Rosaline Chung-Yee Hui; Yu-Huei Huang; Ruey-Yun Huang; Kai-Lung Chen; Ya-Chu Tsai; Po-Ju Lai; Ting-Shun Wang; Tsen-Fang Tsai (Medical Journals Sweden, 2018)
Safety data for secukinumab in patients with psoriasis and viral hepatitis are lacking. The aim of this study is to investigate the risk of reactivation of hepatitis B virus (HBV)/hepatitis C virus (HCV) in patients with psoriasis who are receiving secukinumab therapy. This multicentre study screened 284 patients with psoriasis with available HBV and HCV serological data and 63 patients with concurrent HBV/HCV infection were enrolled. In the absence of antiviral prophylaxis, 7 of 46 (15.2%) patients with HBV exhibited HBV reactivation during secukinumab therapy. The risk of reactivation was significantly higher in HBsAg-positive patients, compared with HBsAg-negative/HBcAb-positive patients (24.0% vs. 4.17%, p = 0.047). One of 14 (7.1%) HCV patients showed enhanced replication of HCV with hepatitis. No virus reactivation occurred in patients receiving antiviral prophylaxis. HBsAg-positive and HBsAg-negative/HBcAb-positive psoriasis patients can develop virus reactivation during secukinumab therapy, thus necessitating close monitoring of viral load and considering an antiviral prophylaxis for all HBsAg-positive patients with psoriasis.